A case report of transverse testicular ectopia with testicular microlithiasis. Issue 8 (7th November 2014) - Lam, Qiqi; Miles, Gemma; Marsdin, Emma; McInerney, Paul; Freeman, Simon
ABSTRACT Transverse testicular ectopia is a rare congenital anomaly in which both testes migrate along the same inguinal canal toward the scrotum. This report describes the case of the rarest form of transverse testicular ectopia in a 23‐year‐old man with coexisting testicular microlithiasis in one of the two testes as diagnosed on sonography and confirmed on MRI. We are unaware of any previous published reports of this association. Although the etiology of both conditions is debatable, each is believed to be associated with an increased risk of testicular malignancy, and this poses a dilemma for the future management of this patient. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound 43:520–523 2015